FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA DOSEN AKUNTANSI - Trisnaningsih, Sri (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
Performance of lecturer is strongly influenced by the behavior of organization commitmentand professional commitmen that are the foundation for the acting or the direction inperforming tasks. Research in the first year study the performance of lecturer related aspectsof behavior that affect the performance of lecturer. The variables in this research include:performance of lecturer, organization commitmen, professional commitment and motivation.The research population is lecturer at PTS in East Java. Sample selection procedure isdetermined by using random sampling method. Technical analysis and hypothesis testing areusing multiple regression tools. The result of first year research shows that motivationsignificantly influences the performance of lecturer.Keywords:performance of lecturer, organization commitment, profession commitment,motivation.